The Dual-Edged Sword: Risks and Benefits of JAK Inhibitors in Infections - Anders Jarneborn; Pradeep Kumar Kopparapu; Tao Jin (Pathogens)
Janus kinase inhibitors (JAKis) represent a relatively new class of immunomodulatory drugs with potent effects on various cytokine signalling pathways. They have revolutionized the treatment landscape for autoimmune diseases such as rheumatoid arthritis, psoriatic arthritis, and ulcerative colitis. However, their ability to modulate immune responses presents a dual-edged nature, influencing both protective immunity and pathological inflammation. This review explores the complex role of JAKis in infectious settings, highlighting both beneficial and detrimental effects. On the one hand, experimental models suggest that JAK inhibition can impair host defence mechanisms, increasing susceptibility to certain bacterial and viral infections. For example, tofacitinib-treated mice exhibited more severe joint erosions in Staphylococcus aureus (S. aureus) septic arthritis and showed impaired viral clearance in herpes simplex encephalitis. Additionally, clinical data confirm an increased risk of herpes zoster in patients receiving JAKis, underscoring the need for rigorous monitoring. On the other hand, JAK inhibition has demonstrated protective effects in certain infectious and hyperinflammatory conditions. In sepsis models, including cecal ligation and puncture (CLP) and S. aureus bacteraemia, tofacitinib improved survival by attenuating excessive inflammation. Furthermore, JAKis, particularly baricitinib, have shown substantial efficacy in mitigating cytokine storms during severe COVID-19 infections, leading to improved clinical outcomes and reduced mortality. These observations suggest that JAKis have a role in modulating hyperinflammatory responses in select infectious contexts. In conclusion, JAKis present a complex interplay between immunosuppression and immunomodulation. While they increase the risk of certain infections, they also show potential in managing hyperinflammatory conditions such as cytokine storms. The key challenge is determining which patients and situations benefit most from JAKis while minimizing risks, requiring a careful and personalized treatment approach.